2005
DOI: 10.1002/ppul.20227
|View full text |Cite
|
Sign up to set email alerts
|

Skin‐prick testing as a diagnostic aid for childhood asthma

Abstract: Diagnosing asthma is problematic when based solely on reported symptoms. The purpose of this study was to evaluate skin-prick testing as a diagnostic aid for asthma in children. Skin-prick testing (SPT) was undertaken in children aged 2-10 years with either no history of wheeze (n = 149) or recent doctor-observed wheeze which responded to treatment with a bronchodilator, the "gold standard" (n = 164). Children with moderate or severe asthma were excluded. SPT positivity increased sharply at age 5 years in whee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 34 publications
0
22
0
6
Order By: Relevance
“…Limited evidence is available regarding the prevalence of sensitisation in preschool children presenting to healthcare workers with wheeze. One study comparing children aged 2-5 yrs with doctor-confirmed wheeze who were responding favourably to a bronchodilator to healthy non-wheezing children found that 32% of wheezy children gave positive skin-prick test results to one or more aeroallergens, compared to 11% of healthy children (likelihood ratio 2.9) [53].…”
Section: Tests Of Sensitisation To Allergensmentioning
confidence: 99%
“…Limited evidence is available regarding the prevalence of sensitisation in preschool children presenting to healthcare workers with wheeze. One study comparing children aged 2-5 yrs with doctor-confirmed wheeze who were responding favourably to a bronchodilator to healthy non-wheezing children found that 32% of wheezy children gave positive skin-prick test results to one or more aeroallergens, compared to 11% of healthy children (likelihood ratio 2.9) [53].…”
Section: Tests Of Sensitisation To Allergensmentioning
confidence: 99%
“…Investigations are also performed to obtain information that may support a diagnosis of asthma. These include tests to confirm atopy [9], such as serum immunoglobulin (Ig)E and the radioallergosorbent test (RAST), assessment of the extent of eosinophilic airway inflammation in bronchoalveolar lavage (BAL) and endobronchial biopsy, and measurement of reticular basement membrane (RBM) thickness in biopsies. This approach is intended to allow subsequent management to be rationalised, with treatment targeted at specific conditions.…”
mentioning
confidence: 99%
“…Kožni testovi izvode se standardnim setom aeroalergena koji su u dobi iznad 5. godina života imaju osetljivost 82% i specifičnost 85% [8].…”
Section: Uvodunclassified